1650-1850 Ideas, Aesthetics, and Inquiries in the Early Modern Era. - Cope, Kevin L.; Cahill, Samara Anne; Barrett, Chris; Choudhury, Mita; Goldmark, Matthew; Hargrave, Jennifer L.; Joseph, Betty; Lythberg, Billie; Mazella, David; Ng, Su Fang (Bucknell University Press, 2022)
Rigorously inventive and revelatory in its adventurousness, 1650-1850 opens a forum for the discussion, investigation, and analysis of the full range of long-eighteenth-century writing, thinking, and artistry. Combining fresh considerations of prominent authors and artists with searches for overlooked or offbeat elements of the Enlightenment legacy, 1650-1850 delivers a comprehensive but richly detailed rendering of the first days, the first principles, and the first efforts of modern culture. Its pages open to the works of all nations and language traditions, providing a truly global picture of a period that routinely shattered boundaries. Volume 27 of this long-running journal is no exception to this tradition of focused inclusivity. Readers will travel through a blockbuster special feature on the topic of worldmaking and other worlds--on the Enlightenment zest for the discovery, charting, imagining, and evaluating of new worlds, envisioned worlds, utopian worlds, and worlds of the future. Essays in this enthusiastically extraterritorial offering escort readers through the science-fictional worlds of Lady Cavendish, around European gardens, over the high seas, across the American frontiers, into forests and exotic ecosystems, and, in sum, into the unlimited expanses of the Enlightenment mind. Further enlivening the volume is a cavalcade of full-length book reviews evaluating the latest in eighteenth-century scholarship.